A low-fidelity serious game for medical-based cultural competence education. (September 2019) - Khan, Zain; Kapralos, Bill
Research has shown that the quality of care is compromised when healthcare providers respond inappropriately to patient language and cultural factors. However, research indicates that medical education is not keeping pace with the changing composition of the patient population in culturally diverse societies such as Canada and the United States, and many healthcare providers do not possess the attitudes or skills required to be effective within a culturally diverse healthcare setting. Here, we present Fydlyty, a web-based, low-fidelity serious game for medical-based cultural competence education. Fydlyty includes both a scenario and dialogue editor providing the ability to develop conversations, interpret responses, and respond to questions/answers from the game player. These responses are based on predefined cultural characteristics of the virtual patient and on different moods that the virtual patient may express depending on the situation. The results of a usability experiment conducted with medical professionals and trainees revealed that the game is easy to use, intuitive, and engaging.